Design And Construction Of Web And Mobile Based Applications For Extracurricular Management (Case Study: MAN 2 Kulon Progo) - Masyitoh, Siti; Handayani, Irma (Kirana Publisher (KNPub), 2024)
MAN 2 Kulon Progo is one of the madrasahs in Kulon Progo that has various extracurricular activities. In the 2023/2024 academic year, MAN 2 Kulon Progo has 24 extracurricular activities. The large number of extracurricular activities certainly attracts students' attention, but the large number of extracurricular activities makes it difficult for the school to record student data, manage extracurricular activities, and there is a risk of errors in data recording. Based on these problems, a web and mobile-based extracurricular management application was built. The purpose of this study is to build an extracurricular management application that can be used by students to register for extracurricular activities and get information about extracurricular activities, extracurricular supervisors can easily manage student data, and extracurricular teachers can manage extracurricular activities more easily.